Comparison of electrochemical deposition and spray methods for Pt and Pd-coated electrodes on porous nickel foam - Isgor, Ismet; Korkut, Sibel Eken; Sari, Fatih Can; Gelir, Ali; Yargi, Onder (SPRINGER HEIDELBERG, 2026)
This study presents a comparative investigation of the electrochemical performance of platinum (Pt) and palladium (Pd)-based electrodes, fabricated via spray coating and electrodeposition techniques on porous nickel foam substrates, for supercapacitor applications. The electrodes were systematically evaluated using cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), specific capacitance analysis, Ragone plot interpretation, and long-term cycling stability tests. CV results revealed that Pt electrodes exhibited wider responses compared to Pd counterparts and the electrodes prepared by using spraying showed better current responses compared to electrodeposited electrodes. The specific capacitance values reach to about 100 F/g at around 0.50 A/g for all electrodes. The energy and power densities for the electrodes between 0.01 and 0.50 A/g current density ranged from 0.1 to 30 Wh/kg and 10 to 20,000 W/kg, respectively. Furthermore, cycling tests up to 4800 cycles demonstrated a consistent increase in capacitance retention for all samples where the sprayed electrodes reached higher values (similar to%120) when compared with the electrodeposited electrodes. In device form, the supercapacitors prepared by the spray coated electrodes showed better performance than the supercapacitors with electrodeposited electrodes.
Keywords: Spray; Deposition; Pt; Pd; Supercapacitor; ATOMIC LAYER DEPOSITION; CARBON SPHERES; PERFORMANCE; SUPERCAPACITORS; PALLADIUM; HYDROGEN; FILMS; MODEL; Chemistry; Electrochemistry; Physics